1996
DOI: 10.1177/0361198196153800103
|View full text |Cite
|
Sign up to set email alerts
|

Walking Distances to and from Light-Rail Transit Stations

Abstract: A quantifiable basis for developing design guidelines for pedestrian access to light-rail transit (LRT) stations is provided for planners based on observations in Calgary, Canada. Calgary's LRT system, which began operations in 1981, has been operating for long enough for walking patterns to and from its stations to become established. Interviews were conducted with 1,800 peak-hour LRT users about the origins and destinations of their LRT trips. Those who walked to or from a station were asked to point out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 0 publications
2
67
1
4
Order By: Relevance
“…There is evidence from the study on walking distances to and from light rail transit stations in the city of Calgary, Canada, that average walking distance to light rail stations is 326 m in the CBD area or 649 m in suburban areas. From this study, perception of walk time was found to vary over the walking environment of stations and 80 m/min was adopted to compare the calculated walking distances with the measured walking distances, which was an approximation to a normal distribution (O'Sullivan and Morrall, 1995). Nevertheless, according to RICS Policy Unit Report (RICS, 2002), the impact area for residential developments could extend to 1000 m from a station depending on the type of investment and the size of the urban area (Du and Mulley, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence from the study on walking distances to and from light rail transit stations in the city of Calgary, Canada, that average walking distance to light rail stations is 326 m in the CBD area or 649 m in suburban areas. From this study, perception of walk time was found to vary over the walking environment of stations and 80 m/min was adopted to compare the calculated walking distances with the measured walking distances, which was an approximation to a normal distribution (O'Sullivan and Morrall, 1995). Nevertheless, according to RICS Policy Unit Report (RICS, 2002), the impact area for residential developments could extend to 1000 m from a station depending on the type of investment and the size of the urban area (Du and Mulley, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Although this approach may be appropriate in urban areas (O'Sullivan and Morrall, 1996), a simple, Cartesian distance cannot estimate the real time and effort required when people had to reach the station on foot -the mode so typical of rural inhabitants who made up the majority of the population until 1931. Hence, our estimates of accessibility take into account two major aspects of geographical space:…”
Section: Pedestrian Accessibility To the Railway Networkmentioning
confidence: 99%
“…The number of riders is related to the type of station (intermediate, terminal, interchange or intermodal). Terminal stations are the nearest stations for residents of a large area beyond the end of the line and people are willing to walk longer to reach this type of station (O'Sullivan and Morrall, 1996). Interchange stations are more attractive for travellers than intermediate stations and tend to capture more riders, while intermodal stations also tend to have higher boardings, since they receive riders from other transport modes.…”
Section: Factors Affecting Ridershipmentioning
confidence: 99%